Análise da decomposição do desempenho de empresas brasileiras utilizando modelos lineares mistos e de componentes de variância - Moraes, Edmilson Alves de (2005)
The delimitation of the main sources of competitive advantage and the quantification of their importance, are still relevant issues in the strategy field of studies. At the middle of the 80´s, a new stream of research emerged, focusing in determining and quantifying the importance of the factors which could explain the differences among the performance of a set of firms, through the decomposition of factors variance using linear regression or variance components. In this set of works, there was developed several empirical researches whose main purpose was to quantify the importance of factors as industrial sector, year, corporate affiliation and idiosyncratic issues in explaining the firm performance. From the results presented in these papers several discussions raised about the hole of corporate strategy and about the relative importance of those factors in the determination of the competitive advantage. The investigation developed in this work, which is aligned with this set of researches, uses a broad and complete data base of Brazilians´ firms, first, to verify if the findings about international firms are similar to Brazilian firms. Second, develop new analysis using linear mixed models, which are theoretically more appropriate for this type of analysis. Third, by the use of two types of covariance matrices, test the existence of repeated measures for the variable year, to verify if the results of performance of a year influence the performance of the subsequent years. Finally, it is analyzed if being established in a specific Brazilian State impacts the firm performance.